Systematic review and meta‐analysis of the clinical effectiveness of bipolar compared with monopolar transurethral resection of the prostate (TURP). (24th October 2013) - Omar, Muhammad Imran; Lam, Thomas B.; Alexander, Cameron E.; Graham, John; Mamoulakis, Charalampos; Imamura, Mari; Maclennan, Steven; Stewart, Fiona; N'Dow, James
Abstract : To compare monopolar and bipolar transurethral resection of the prostate (TURP) for clinical effectiveness and adverse events. We conducted an electronic search of MEDLINE, Embase, CENTRAL, Science Citation Index, and also searched reference lists of articles and abstracts from conference proceedings for randomised controlled trials (RCTs) comparing monopolar and bipolar TURP. Two reviewers independently undertook data extraction and assessed the risk of bias in the included trials using the tool recommended by the Cochrane Collaboration. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. From the 949 abstracts that were identified, 94 full texts were assessed for eligibility and a total of 24 trials were included in the review. No statistically significant differences were found in terms of International Prostate Symptom Score (IPSS) or health‐related quality of life (HRQL) score. Results for maximum urinary flow rate were significant at 3, 6 and 12 months (all P < 0.001), but no clinically significant differences were found and the meta‐analysis showed evidence of heterogeneity Bipolar TURP was associated with fewer adverse events including transurethral resection syndrome (risk ratio [RR] 0.12, 95% confidence interval [CI] 0.05–0.31, P < 0.001), clot retention (RR 0.48, 95% CI 0.30–0.77, P = 0.002) and blood transfusion (RR 0.53, 95% CI 0.35–0.82, P = 0.004) Several major methodological limitations were identified in the included trials; 22/24 trials had a short follow‐up of ≤1 year, there was no evidence of a sample size calculation in 20/24 trials and the application of GRADE showed the evidence for most of the assessed outcomes to be of moderate quality, including all those in which statistical differences were found. Whilst there is no overall difference between monopolar and bipolar TURP for clinical effectiveness, bipolar TURP is associated with fewer adverse events and therefore has a superior safety profile. Various methodological limitations were highlighted in the included trials and as such the results of this review should be interpreted with caution. There is a need for further well‐conducted, multicentre RCTs with long‐term follow‐up data.